The data. - Patel, P. (IEEE spectrum)
In 1874, the University of Berlin refused to grant a doctorate to the Russian mathematical genius Sofya Vasilyevna Kovalevskaya, who turned around and got one at the rival University of GÃ?Â¶ttingen; even so, she had to emigrate to Sweden to find a teaching job. Eight years later in the United States, Johns Hopkins University refused to grant Christine Ladd-Franklin a Ph.D., although she'd done her dissertation under the famous logician Charles Sanders Peirce. The school simply did not grant degrees to women.